Differences in Learning Methods Start With a Question and Question Student Have Against Social Learning Results Proclamation History Indonesian Independence - Asri, Sriawan; Dwiprabowo, Risky (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This study aims to determine whether or not there are differences in the results of social studies learning material on the history of the proclamation of Indonesian independence of students taught by learning methods. Learning Starts With A Question and Question Student Have.Â This study uses a quantitative method with the type of approach "quasi-experimental" and "experimental design posttest-only control group" research sample consisted of 30 students in the experimental class I and 30 students in experiment II. This sampling uses a sample cluster.Â Based on the calculation results obtained an average of X1 66.3 and an average value of X2 93.5 after which the t-test was calculated, then the t-count was obtained at 9.03 with a dk of 58 then obtained a ttable with a significance level of 2.02 . Because tcount> ttable, it can be concluded that H0 is rejected and H1 is accepted, it can be concluded that there are significant differences in the use of learning strategies Learning Starts With A Question And Question Student Have.